VIET TEOREMASÍNAN PAYDALANÍP PARAMETRLI KVADRAT TEŃLEMELERDI SHESHIW USÍLLARÍ - Djumabaev, N. (SCIENCE and SOCIETY, 2023)
This article provides methods for solving quadratic equations with a parameter using Vieta’s theorem.